Design of Dual Band Substrate Integrated Waveguide (SIW) Antenna with Modified Slot for Ka-Band Applications - Agilesh, Saravanan Ramamoorthi; Madhav, Boddapati T. P.; Gangadhar, A.; Chintalapati, Sarada Sowjanya (Engineering, Technology & Applied Science Research, 2024)
This paper introduces a dual-feed substrate integrated waveguide antenna design with a modified H-Slot (DFH-SIW) for Ka-band 5G applications. In general, 5G base stations operating in Ka-band applications need large bandwidth-based antennas with high gain to solve the problem of path loss and high data capacity. To resonate with an ideal bandwidth at 28/38 GHz, this study proposes a high-gain antenna with a modified H-slot. This study used the CST EM tool to design the proposed antenna model and evaluate and optimize its characteristics. The proposed dual feed antenna has compact dimensions of 12×12×1.2 mm and was constructed on a Roger 5880 substrate with an appropriate permittivity of 2.2 and a minimal loss tangent of 0.0009. The proposed dual-feed antenna showed an ideal reflection coefficient of less than -10dB and a bandwidth of 3.7 GHz and 3.23 GHz at operating frequencies of 28 and 38 GHz, respectively. The proposed design operates at the 28 GHz frequency with 73.2% efficiency and 4.3 dBi gain, and at 38 GHz with 83.68% efficiency and 6.7 dBi gain. This antenna is intended to be used in future 5G wireless networks and has outstanding overall performance in terms of return loss, gain, and wide bandwidth.